(untitled) - Dougherty, Peter J. (New York, 2002)
In the course of his argument, Dougherty follows Adam Smith’s ideas through several generations of economic thought, from nineteenth-century economic philosophers such as Alfred Marshall, who maintained a focus on moral sentiments while extending the field’s technical reach, to twentieth-century giants such as John Maynard Keynes, Paul Samuelson, and Milton Friedman, whose analytical economics have served to defend and expand market democracy.
Keywords: Capitalism,Economics,Globalization,Business ethics,Đạo đức kinh doanh,Nền kinh tế,Toàn cầu hóa; Moral and ethical aspects,Moral and ethical aspects,Moral and ethical aspects,Khía cạnh lương tâm và đạo đức,Khía cạnh lương tâm và đạo đức